On Zeros of Periodic Zeta Functions - Laurinčikas, A.; Šiaučiūnas, D. (Український математичний журнал, 2013)
We consider zeta functions ζ(s; a) given by Dirichlet series with multiplicative periodic coefficients and prove that, for some classes of functions F , the functions F(ζ(s; a)) have infinitely many zeros in the critical strip. For example, this is true for sin(ζ(s; a)). Розглянуто дзета-функції ζ(s; a ), що задані рядами Діріхлє з мультиплікативними періодичними коефiцiєнтами, та доведено, що для деяких класів функцій F функції F(ζ(s; a )) мають нескінченну кількість нулів у критичній смузі. Наприклад, це виконується для sin(ζ(s; a )).